L’organizzazione dello spazio sonoro della polifonia rinascimentale: un precoce caso di ‘presentismo’ nella storia della musicologia? - Daniele Sabaino (Musica Docta)
Reading the past solely through the lens of the present can take several forms. The most obvious is the reading that uses contemporary ethical/moral categories to evaluate and discriminate against past cultural positions, resulting in various forms of the so-called “cancel culture” that we have witnessed in recent years, including in many academic settings. I believe, however, that the “presentism” we are addressing in this group meeting is also at work in seemingly less obvious situations, such as the outright denial (or, more subtly, the “suspension”) of historical perspective per se. This may be motivated by perfectly respectable claims of scientific caution, but in the end it cannot help but deny the contemporary researcher not only (and rightly) the possibility of direct access to the socio-cultural contexts of the past, but also the ability to read, however critically, past cultural phenomena through hermeneutic categories derived from that same past. As an example of the above, I will describe a highly representative case from a research topic that I have been working on for many years, namely the organisation of tonal space in Renaissance music. Building, among other things, on an intuition of Frans Wiering, Marco Mangani and I have tried to reconstruct what can be called “inevitable presentism”, that is, the recognition that cultural phenomena of the past can, for obvious reasons, only be observed from outside the culture that produced them. For us, this means fulfilling a duty of scholarship in the humanities: to enter into dialogue with the past with our contemporary questions and methodologies, without weakening historical consciousness.